Special physical training method for beginner group artistic gymnastics - Bezhentseva, L. M. (Theory and Practice of Physical Culture, 2020)
Presently the research community is far from agreement on the ideal theoretically grounded recommendations on what age is the best for progress in the group rhythmic gymnastics. Many authors acknowledge benefits of the traditional beginner training system with the primary all-round physicality and skills formed by individual trainings with/ without apparatuses; with no group exercises recommended for the age group. Objective of the study was to test benefits of a new special physical training method for beginner group rhythmic gymnastics. The training method was tested in 2017-18 school year at the Y. Kuznetsov CYORSS in Seversk, with the 7-8 year old beginner female gymnasts (n=30) sampled for the study and split up into Experimental and Reference Groups (EG, RG) of 15 people each. The Reference Group training process was traditional, whilst the Experimental Group trainings were dominated by the special physical training method to master the key motor skills and develop the sport-specific physical qualities. The experimental method was tested beneficial as verified by the Experimental Group versus Reference Group physical progress and skills tests.